ACUTE TOXICITY AND BIOACCUMULATION OF ZINC AND LEAD IN THE FRESHWATER PRAWN MACROBRACHIUM LANCHESTERI - Othman M, Shuhaimi; Azwa M, Nor (Malaysian Journal of Science, 2004)
Adults of Macobrachium lanchesteri were exposed for a nine-day period under laboratory conditions to a range of zinc and lead concentrations. Mortality was assessed and median lethal times (LT50) and concentrations (LC50) were calculated. At the end of nine-day period, prawns that survived were used to determine bioaccumulation of the metals. LT50 and LC50 increased with decrease in mean exposure concentrations and times respectively for the two metals (Zn and Pb). LC50s for 24,48 and 96 hours for zinc were 1230, 1054 and 395 µg/L and for lead 269, 194 and 123 µg/L respectively. Zinc and lead bioaccumulation in M lanchesteri increased with increasing concentration of exposure and lead was more toxic than zinc to M lanchesteri (Pb>Zn).